2021
DOI: 10.1002/srin.202100273
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence State and Behavior of Carbon Brick Brittle in a Large Dissected Blast Furnace Hearth

Abstract: The thickness of the carbon bricks is one of the important factors of the longevity of the blast furnace. Herein, a large number of brittle carbon bricks in the hearth sidewall and the continuous rectangle‐shape floating refractory in residual iron are found during the blast furnace hearth dissection. The occurrence state of the carbon brick is characterized through chemical analysis, X‐ray diffraction (XRD), and scanning electron microscope (SEM)–energy‐dispersive X‐ray spectroscopy (EDS). The contents of K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It can also be obtained from Figure , especially the small particles accounted for a large proportion in S4. It was worth noting that some small coke particles may float to the tuyere until they were burned where η is the coke consumption rate (%), d lower coke is the coke diameter in the lower parts of the blast furnace (mm), and d upper coke is the coke diameter in the upper parts of the blast furnace (mm).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…It can also be obtained from Figure , especially the small particles accounted for a large proportion in S4. It was worth noting that some small coke particles may float to the tuyere until they were burned where η is the coke consumption rate (%), d lower coke is the coke diameter in the lower parts of the blast furnace (mm), and d upper coke is the coke diameter in the upper parts of the blast furnace (mm).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…In previous blast furnace dissections, it was found that alkalis were enriched at different height levels of the blast furnace 27) , and the accumulation times of K and Na in the blast furnace can reach 50 times 28) . Alkalis could cause deterioration of coke performance 11) and damage to carbon bricks [3][4][5] . After a large amount of alkalis enters the hearth, it would worsen the active state of the hearth and increase the erosion of carbon bricks.…”
Section: Trace Elements In Slagmentioning
confidence: 99%
“…As a key area for storing slag and iron in the blast furnace, hearth is the limiting aspect of the long life of the blast furnace. In recent years, a large number of blast furnace anatomical studies have found that the enrichment of trace elements in the hearth plays a crucial role in the safe operation of the blast furnace hearth [3][4][5][6][7][8][9][10] . The cyclic enrichment of harmful elements (K, Na, Zn) in the blast furnace aggravates the erosion of the carbon bricks [3][4][5][6] and also deteriorates the metallurgical properties of the coke 11,12) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the carburization behavior of molten iron on refractories also governs the lifespan of blast furnaces. [ 6 ] Thus, understanding the wetting behavior of molten iron on carbonaceous refractories is indispensable for exploring a path toward low‐carbon emissions and prolonged lifespan in blast furnace smelting.…”
Section: Introductionmentioning
confidence: 99%